Correlates of food insecurity among university students in a socioeconomically disadvantaged area of the Paris suburbs: A cross-sectional study - Henri Dehove; Malo Mofakhami; Julia Baudry; Emmanuelle Kesse-Guyot; Chantal Julia; Mathilde Touvier; Sandrine Péneau; Alice Bellicha (PLoS ONE, 2025)
Background Despite increasing political and scientific interest in food insecurity (FI) among higher education students, data for Europe remain scant. We assessed the prevalence of FI at a French university located in a disadvantaged area in the outskirts of Paris, and its associations with perceived academic dropout and socioeconomic, demographic, and lifestyle factors. Methods We conducted a cross-sectional online survey among 5068 students (22% of overall population, 66% women). FI status was defined by a three-level class variable (quantitative FI: “not having access to enough food”, qualitative FI: “not having access to the desired food”, food security: “having access to enough desired food”). Multivariate multinomial logistic regression models found associations between (i) FI and academic dropout and (ii) socioeconomic, demographic, academic-related data, cooking and eating conditions, and FI. Results Students reporting quantitative FI (11%) or qualitative FI (35%) more often experienced academic dropout ( p < 0.0001). Men more often reported quantitative FI ( p < 0.0001). Living in a collective residence, lacking sufficient household cooking facilities, experiencing financial difficulties, using food assistance, being an undergraduate, having obtained a high-school diploma abroad, not receiving food from family, regularly eating alone, and infrequent cooking were positively associated with both quantitative and qualitative FI ( p < 0.0001). Conclusion We found elevated rates of FI among university students and an association between FI and academic dropout. Structural and behavioural factors were found to be associated with FI. These findings provide insight into the characteristics of those students most likely to experience FI and suggest testable preventive actions.